A systematic review of empirical studies on the types of vocabulary learning strategies used by EFL learners in higher education - Yan, Tiantian (My University, 2023)
Considering that many empirical studies on the types of vocabulary learning strategies used by EFL learners in higher education indicated similar and different results, this systematic synthesizes the findings of the included empirical studies on vocabulary learning strategies employed by EFL learners in higher education to provide a comprehensive understanding of the types of vocabulary learning strategies used by EFL learners across included countries, identify the similar and different results between the included studies, and explore potential reasons for the similarities and differences. A convergent qualitative synthesis approach was adopted for this systematic review. Inclusion and exclusion criteria were utilized in data collection process, and Excel was used as a tool for information recording and coding in data analysis. The data was collected within a time span from 2013 to 2022 in EBSCO (Education Source), resulting in 18 empirical studies being included. The findings of this study indicate that EFL learners in higher education mainly used seven types of vocabulary learning strategies including determination, cognitive, memory, metacognitive, social/affective, compensatory and technology-based strategies. Moreover, common trends were identified in using determination, social and technology-based strategies based on 18 included studies, and differences existed in using strategies such as memory and metacognitive strategies. The potential factors such as learning environments, academic majors, levels of English proficiency, previous learning experiences and beliefs for the similarities and differences were explored to provide a more comprehensive understanding of the similar and different results. Research gaps, future research directions and pedagogical implications were also explored and suggested.
Keywords: vocabulary learning strategies, EFL learners, higher education, systematic review